Effects of Front Plate Geometry on Brush Seal in Highly Swirling Environments of Gas Turbine - Yuxin Liu (MDPI AG, 2021)
Advanced brush seal technology has a significant impact on the performance and efficiency of gas turbine engines. However, in highly inlet swirling environments, the bristles of a brush seal tend to circumferentially slip, which may lead to aerodynamic instability and seal failure. In this paper, seven different front plate geometries were proposed to reduce the impact of high inlet swirl on the bristle pack, and a three-dimensional porous medium model was carried out to simulate the brush seal flow characteristics. Comparisons of a plane front plate with a relief cavity, plane front plate with axial drilled holes, anti-“L”-type plate and their relative improved configurations on the pressure and flow fields as well as the leakage behavior were conducted. The results show that the holed front plate can effectively regulate and control the upstream flow pattern of the bristle pack, inducing the swirl flow to move radially inward, which results in decreased circumferential velocity component. The anti-“L” plate with both axial holes and one radial hole was observed to have the best effect on reducing the swirl of those investigated. The swirl velocity upstream the bristle pack can decline 50% compared to the baseline model with plane front plate, and the circumferential aerodynamic forces on the bristles, which scale with the swirl dynamic head, are reduced by a factor of 4. This could increase the bristle stability dramatically. Moreover, the front plate geometry does not influence the leakage performance significantly, and the application of the axial hole on the front plate will increase the leakage slightly by around 3.5%.